The role of digitalization of libraries in ensuring the humanitarian security of society - Lomachinskyi , Bohdan (Skhid, 2023)
The article analyzes the peculiarities of the of Ukrainian digital libraries formation and their role in ensuring the humanitarian security of society. The relevance and novelty of the study lies in the clarification of the need for digitization of library funds and the creation of a national system of digital libraries as a significant coun-termeasure in the worldview (conscientious) wars of today. It has been established that the digital epoch forms a new type of person - a "digital person", which sets to the library the task of developing new strategies for library service, based on knowledge management and increasing the level of digital competences of both library workers and library users for the effective accumulation of personal and so-cial digital capital. The essential features of digital libraries, their advantages com-pared to traditional libraries are analyzed; the peculiarities of the formation of digital libraries are determined, taking into account the world and Ukrainian experience. It is noted that in the Ukrainian library space, the leading place in the digitization of na-tional cultural heritage is occupied by the V. Vernadsky National Library of Ukraine, on the basis of which the national electronic library "Ukrainika" was created, which aims to collect in digital format works about the Ukrainian people, the territory of Ukraine and about all peoples who lived or live in this territory. This will provide users of the electronic library with knowledge about the history of Ukraine, its traditions and culture, the Ukrainian nation and statehood, and its place in the world civiliza-tional development. It was established that the issue of digitization of library re-sources requires additional attention to the problem of their protection, in order to ensure the confidentiality, integrity and availability of their information resources. The conclusions emphasize that the digitization of the national book heritage for the preservation of national memory and identity is a promising strategy for countering conscientious wars.